Sequenciamento do genoma e identificação de candidatos a efetores de Hemileia vastatrix - Porto, Brenda Neves (2016)
Coffee rust caused by the fungus Hemileia vastatrix (Berkely & Broome) is responsible for the main leaf disease that affects the production of Coffea arabica L. When chemical control is not used, this disease can cause losses of up to 50% of the production. The use of coffee cultivars resistant to H. vastatrix (Hv) is the most efficient strategy for controlling this disease. However, obtaining resistant genotypes has been a challenge due to the high adaptation potential of the fungus and, consequently, the emergence of new physiological strains of the pathogen, which overcome cultivar resistance. During the interaction with coffee, the fungus secret a lot of effector proteins that modify the structure and function of the host cell, allowing or not the establishment of infection, depending on the host genotype. Functional genomics studies are enlightening the molecular mechanisms involved in the plant-pathogen interaction and the development of molecular techniques for identification of individual isolates should be pursued. The objective of this work was to sequence the whole genome of this fungus and identify genes that may contribute for microbial pathogenicity or host resistance. Using a strategy of hybrid assembly and two new generation sequencing platforms, PacBio RS II and Illumina – HiSeq 2500, we obtained a partial genome of the isolate HV-02 (strain XXXIII of Hv) with the size of 576 Mb. We verified that 96.37% of the conserved eukaryotes genes were present in the annotated Hv genome, indicating an elevated level of integrity during the assembly process, being coded 13,034 proteins. The similarity analysis of the proteins predicted in the genome and the protein sequences between Hv and other fungi showed that 74% hit within the Pucciniales order, especially with Puccinia graminis f. sp. tritici and Melampsora larici-populina, and 12% presented no similarity with any protein described in the analyzed databanks, being considered exclusive to Hv. With the deduced proteome, we predicted the functional secretome. We identified 615 signal peptide containing proteins located in the secretion pathway and with no transmembrane domains. Within the obtained secretome, 111 proteins were considered candidates for specific Hv effectors. We selected 17 putative genes (EHv33) to be validated by real-time PCR. The analyses of temporal expression of these genes (EHv33) showed that most of them were significantly up regulated after the formation of haustoria, in the compatible interaction, and can be considered candidate genes for effectors translocated via haustoria.